Three new species of Graphidaceae from tropical Africa - Broeck, Dries Van Den; Lücking, Robert; Ertz, Damien (Phytotaxa, 2014)
Three new species of Graphidaceae are described as new to science from tropical Africa: Graphis aptrootiana Van den Broeck, Lücking & Ertz and Redingeria desseiniana Van den Broeck, Lücking & Ertz from the Democratic Republic of the Congo, and G. vandenboomiana Ertz, Lücking & Van den Broeck from Reunion. A key is presented to all known species of Redingeria. The lichenicolous fungus Etayoa trypethelii is mentioned as new to Central Africa.